ANALYSIS OF PARAMETRIC STUDIES AND A NEW PROPOSED CORRELATION OF OIL RECOVERY FACTOR ESTIMATION FOR STEAMFLOODING PERFORMANCE BY CONSIDERING INJECTION PATTERN PARAMETER - TJA, KEVIN
Steamflooding simulation has been well proven to predict the performance of the fields having heavy reservoir fluid type. Currently, there are still few references about simple prediction methods of oil recovery. Therefore, it is necessary to conduct analysis of any parameters that can affect the value of recovery factor in the field applying the steamflooding. In the study, Field X, classified as heavy oil field, is used and the investigated parameters are injection pattern, permeability, viscosity, duration of injection time and bottom-hole pressure (BHP). The study have been conducted by a reservoir simulation model to produce some significant parameters and then by using the Two Level Full Factorial Design of Experiment (DOE) method to obtain the relationship between the tested parameters and the value of recovery factor. The results obtained by Design of Experiment (DOE) show that the parameters which have the greatest impact on recovery factor are permeability, viscosity, injection pattern, injection duration and bottom-hole pressure (BHP) injection well respectively which showing permeability and viscosity is about 1.75 - 2 times stronger effect than the pattern, duration, and BHP. Furthermore, the produced correlation has an equation of RF = -6.70 + 6.51 Pattern + 0.01324 k - 0.02854  + 0.662 t + 0.0446 BHP with R2 of 92.02% which is considered quite high. The comparison of recovery factor results between Myhill and Stegemeier (1978), Wiriando (2016) and this study show that WiriandoÃ‚Â’s and this study yield similar results but Myhill and StegemeierÃ‚Â’s prediction is almost twice as WiriandoÃ‚Â’s and this study.